Measure Functional Differential Equations in the Space of Functions of Bounded Variation. (23rd September 2013) - Afonso, S. M.; Rontó, A.
Abstract : We establish general conditions for the unique solvability of nonlinear measure functional differential equations in terms of properties of suitable linear majorants.